PENGARUH KONSENTRASI AIR KELAPA (Cocos nucifera L.) TERHADAP EKSPLAN KRISAN (Chrysanthemum morifolium) KULTIVAR ‘XANNE AGRIHORTI’ SECARA IN VITRO - Sri Fitri Solihah; Ateng Supriyatna; Ayuni Adawiyah (UIN Sunan Gunung Djati Bandung, 2021)
Krisan (Chrysanthemum morifolium) Cultivars ‘Xanne Agrihorti’ is one of the most popular ornamental plants in Indonesia. One of the problems that arise in the cultivation of chrysanthemums is the high cost of growth regulators. Coconut water contains growth regulators in the form of high cytokinins. The purpose of this study was to determine the effect of coconut water on the growth of krisan (Chrysanthemum morifolium) Cultivars ‘Xanne Agrihorti’ in vitro and determine the optimal concentration of coconut water in the growth of chrysanthemum plants in vitro. This study used a Completely Randomized Design (CDR), with concentration of coconut water which consisted of 4 treatment levels : 0 ml/liter, 100 ml/liter, 150 ml/liter, 200ml/liter. The experiment was carried out 3 times, so the experimental units were 12. Parameters measured were number of shoots, number of roots, stem height, root length and survival rate. Data analysis used the Kruskal-Wallis test. The data obtained after being analyzed statistically through the Kruskal-Wallis test at a confidence level of p<0,05. The results showed that the addition of coconut water with a coconut water had an effect on the growth and development of tissue culture with a concentration of 150 ml/L gave optimal results for the formation of the number of leaves as many as 11 leaves, concentration of 100 ml/L gave the best results for the formation of the number of roots as much as 10 roots, and the percentage of survival was 100%.